Single-dose rAAV5-based vaccine provides long-term protective immunity against SARS-CoV-2 and its variants - Guochao Liao; Hungyan Lau; Zhongqiu Liu; Chinyu Li; Zeping Xu; Xiaoxiao Qi; Yu Zhang; Qian Feng; Runze Li; Xinyu Deng; Yebo Li; Qing Zhu; et al. (Virology Journal, 2022)
Abstracts The COVID-19 pandemic, caused by the SARS-CoV-2 virus and its variants, has posed unprecedented challenges worldwide. Existing vaccines have limited effectiveness against SARS-CoV-2 variants. Therefore, novel vaccines to match mutated viral lineages by providing long-term protective immunity are urgently needed. We designed a recombinant adeno-associated virus 5 (rAAV5)-based vaccine (rAAV-COVID-19) by using the SARS-CoV-2 spike protein receptor binding domain (RBD-plus) sequence with both single-stranded (ssAAV5) and self-complementary (scAAV5) delivery vectors and found that it provides excellent protection from SARS-CoV-2 infection. A single-dose vaccination in mice induced a robust immune response; induced neutralizing antibody (NA) titers were maintained at a peak level of over 1:1024 more than a year post-injection and were accompanied by functional T-cell responses. Importantly, both ssAAV- and scAAV-based RBD-plus vaccines produced high levels of serum NAs against the circulating SARS-CoV-2 variants, including Alpha, Beta, Gamma and Delta. A SARS-CoV-2 virus challenge showed that the ssAAV5-RBD-plus vaccine protected both young and old mice from SARS-CoV-2 infection in the upper and lower respiratory tracts. Whole genome sequencing demonstrated that AAV vector DNA sequences were not found in the genomes of vaccinated mice one year after vaccination, demonstrating vaccine safety. These results suggest that the rAAV5-based vaccine is safe and effective against SARS-CoV-2 and several variants as it provides long-term protective immunity. This novel vaccine has a significant potential for development into a human prophylactic vaccination to help end the global pandemic.